PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS TEKNOLOGI DIGITAL - Saragih, Sri Rahmah Dewi; Sari, Putri Lidiana Permata; Suciati, Raihana Tresna; Putri, Riska Amelia; Aulia, Rizki; Arianti, Sri Dita; Safira, Ayu; Hasanah, Hikmatun; Hariyanti, Hariyanti; Harahap, Ramona; Amalia, Amalia; Manurung, Intan Zarina; Putri, Hilya (Smart Education, 2025)
The training for creating digital technology-based mathematics learning media at SMA N 1 Pulau Rakyat on October 2, 2024, aimed to enhance the quality of mathematics education in the digital era. Involving one lecturer and eleven students, this activity adopted interactive methods to foster better student engagement in learning. Initial observations revealed that many students struggled to understand mathematical concepts due to conventional teaching methods. This training focused on introducing digital tools, where students learned to create learning media such as interactive posters and infographics. Evaluation results showed an increase in students' confidence in using technology and their interest in mathematics. Thus, this program not only improves mathematical understanding but also develops relevant technological skills, making students active creators in the learning process.Keywords: Learning media, Digital technology, Mathematics education, Student engagement.